2008
DOI: 10.1007/s00125-008-1036-6
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Jnk1 and Jnk2 accelerates basal lipolysis and promotes fatty acid re-esterification in mouse adipocytes

Abstract: Aims/hypothesis Elevated plasma levels of NEFA impair insulin action. Given the positive linear correlation between NEFA released by adipocytes and plasma NEFA levels, identification of mechanisms controlling adipocyte lipolysis and NEFA release could provide a guide to new therapies for insulin resistance and type 2 diabetes. Methods Short hairpin RNA-mediated gene ablation was used to determine the functions of c-Jun N-terminal kinase (JNK)1 and JNK2 in adipocytes. Results Combined JNK1/JNK2 deficiency drast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
4
14
0
Order By: Relevance
“…Regarding the role of JNK activation in the regulation of lipolysis, it was described that JNK1/JNK2 defi ciency drastically enhanced basal lipolysis ( 24 ). In this context, our data show that incubation with the JNK inhibitor SP600125 (2 h) stimulates the phosphorylation of HSL at Ser 563 and Ser 660 as well as phospho-PKA substrate/perilipin ratio, supporting the idea that JNK inhibition leads to increased lipolysis.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Regarding the role of JNK activation in the regulation of lipolysis, it was described that JNK1/JNK2 defi ciency drastically enhanced basal lipolysis ( 24 ). In this context, our data show that incubation with the JNK inhibitor SP600125 (2 h) stimulates the phosphorylation of HSL at Ser 563 and Ser 660 as well as phospho-PKA substrate/perilipin ratio, supporting the idea that JNK inhibition leads to increased lipolysis.…”
supporting
confidence: 84%
“…In addition to the PKAmediated phosphorylation, HSL may be phosphorylated by other kinases, such as extracellular signal-regulated kinase (ERK1/2), which activates HSL by phosphorylation on Ser 600 ( 23 ). It has been suggested that c-Jun N-terminal kinase (JNK) could play a role in the regulation of lipolysis based on the fact that silencing of Jnk1 and Jnk2 accelerates basal lipolysis in mouse adipocytes ( 24 ).…”
Section: Analysis Of Mrna Levelsmentioning
confidence: 99%
“…UV-or arsenite-induced apoptosis of fibroblasts required both JNK1 and JNK2 (191,192). In addition, lipolysis in adipocytes was also regulated by JNK1 and JNK2 (193). The results of these studies suggest that the different JNKs can act in a concerted manner in some cell and stimulus contexts.…”
Section: Comparison Of Jnk1 and Jnk2 Functions In Vivomentioning
confidence: 76%
“…by guest, on May 11, 2018 www.jlr.org Downloaded from metabolism in mouse adipocytes ( 43 ). Our recent study showed that JNK2, but not JNK1, mediates regulation of CIDEC expression by insulin in human adipocytes ( 23 ).…”
Section: Jnk2 Mediates Insulin-induced Upregulation Of Lipogenic Enzymentioning
confidence: 88%